2001
DOI: 10.1051/0004-6361:20010877
|View full text |Cite
|
Sign up to set email alerts
|

Charge-equilibration of Fe ions accelerated in a hot plasma

Abstract: Abstract.We examine the energy-dependent rates of charge-changing processes of energetic Fe ions in the hot plasma of the solar corona. For ionization of the Fe-ion projectile in collisions with ambient protons, three different methods of estimating the corresponding ionization cross sections are presented and compared. Proton-impact ionization is found to be significant irrespective of the particular method used. Differences in the proton-impact ionization cross sections' estimates are shown to have little ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 24 publications
(33 reference statements)
1
27
0
Order By: Relevance
“…This is because processes such as: (1) chargechanging effects resulting from ionization by thermal electrons and ions, (2) mixing of sources with different ionic charge distributions, and (3) M/Q-dependent energy spectra, do not significantly affect the ionic charge states as a function of energy (see e.g., Kovaltsov et al 2001;Klecker et al 2007). …”
Section: Ionic Charge States In Gradual Sepsmentioning
confidence: 99%
“…This is because processes such as: (1) chargechanging effects resulting from ionization by thermal electrons and ions, (2) mixing of sources with different ionic charge distributions, and (3) M/Q-dependent energy spectra, do not significantly affect the ionic charge states as a function of energy (see e.g., Kovaltsov et al 2001;Klecker et al 2007). …”
Section: Ionic Charge States In Gradual Sepsmentioning
confidence: 99%
“…In these models, the large variability of the increase of Q with energy can be reproduced by variable acceleration rates and non-equilibrium conditions for charge stripping (e.g. Kovaltsov et al, 2001). In the case of near-equilibrium conditions (as observed in the 6 November, 1997 event) and acceleration time scales of ∼1-100 seconds, this corresponds to coronal densities of 10 8 -10 10 cm −3 , i.e.…”
Section: Ionic Charge Composition In Interplanetary Shock-related Eventsmentioning
confidence: 98%
“…The amount of electron stripping depends on the product of the density in the acceleration region (n) and the acceleration time ('r). To strip MeV/nucleon Fe requires m ::::<10 10 s/cm 3 (Kovaltsov et al, 2001). However, there is a correlation between the Fe/O ratio and the mean charge state of Fe (Moebius et al, 2000;Labrador et al, 2003), as shown in Figure 4.…”
Section: New Observations Of Impulsive and Gradual Eventsmentioning
confidence: 99%
“…Perhaps high-energy particles traverse more material during acceleration and are stripped of additional electrons (Ruffolo, 1997, Reames, Ng, and 1jJlka, 1999, Barghouty and Mewaldt, 2000Kocharov, Kovaltsov, and Torsti, 2001). The amount of electron stripping depends on the product of the density in the acceleration region (n) and the acceleration time ('r).…”
Section: New Observations Of Impulsive and Gradual Eventsmentioning
confidence: 99%